Phytochemical Characterization of Taxus baccata L. Aril with Emphasis on Evaluation of the Antiproliferative and Pro-Apoptotic Activity of Rhodoxanthin - Daria-Antonia Dumitraş; Andrea Bunea; Dan Cristian Vodnar; Daniela Hanganu; Emoke Pall; Mihai Cenariu; Adrian Florin Gal; Sanda Andrei (Antioxidants, 2022)
Taxus baccata L., an evergreen tree, was known until recently due to its high concentration of toxic compounds. The purpose of the present study was to focus on the only non-poisonous part, the red arils, which have recently been described as an important source of various bioactive constituents. To establish total phenolic, flavonoid, and carotenoid content, antioxidant capacity, and cytotoxic properties, two types of extracts were obtained. The chemical profile of the ethanolic extract was evaluated using chromatographic (HPLC-DAD-ESI+) and spectral (UV-Vis) methods, and the antioxidant activity of the ethanolic extract was assessed using DPPH and FRAP assays, yielding moderate results. In the second type of extract (methanol: ethyl acetate: petroleum ether (1:1:1, v/v/v)) we identified three carotenoids using open column chromatography and RP–PAD–HPLC, with rhodoxanthin being the most abundant. Considering the above and mainly because of the lack of information in the literature about this pigment and its biological effects, we decided to further investigate the cytotoxic activity of rhodoxanthin, the main carotenoid presented in aril, and its protective effect against H2O2-induced oxidative stress using two cell lines: human HaCaT keratinocytes and B16F10 murine malignant melanoma. The MTT and Annexin-V Apoptosis assays showed a substantial cytotoxic potential expressed in a dose-dependent manner towards the melanoma cell line, however, no obvious cytotoxic effects on human keratinocytes were noticed.